The Role of Islamic Education in Positive Social Transformation amidst Technological Advancements - Suratin, Sonia Isna; Prayogo, Pandu; Munawarsyah, Muzawir; Lestari, Rizki (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
Social change, which progresses in tandem with technological advancements, significantly impacts all aspects of life, including education. Education must strive to withstand the tides of change that challenge existing values and norms. Social change is further accelerated by developments in telecommunications, social media, and globalization, which have profound implications for the paradigm of Islamic education. This study aims to analyze the role and strategies of education in surviving amidst these continual changes. It emphasizes the contributions of education and its ability to endure by examining Q.S. Ar-Ra’d Verse 11 and Sahih Muslim No. 4034. Employing qualitative library research with a descriptive-narrative approach, this study collected data through textual analysis of relevant sources. The data were classified into thematic discussions and analyzed using content analysis techniques, subsequently structured into a systematic narrative article. The findings reveal that social transformation and education are two inseparable elements. In the context of Islam, education not only focuses on knowledge development but also integrates moral and ethical values, promoting social engagement. Education is regarded as the key to positive social change and must continuously adapt to the evolving times to meet the changing needs of humanity.